Consumer Perception of Healthy Food Quality and Service Quality: Case Study at Mie Gacoan Citra Raya Tangerang Outlet - Vanit, Familia Dasil; Separgo, Firlea Zevanka; Tanadi, Leon (Corespub, 2025)
Mie Gacoan is a restaurant company that offers spicy noodle-based products, dimsum, and beverages with a unique concept inspired by the characteristics of Indonesian ghosts. Established in 2016, Mie Gacoan is rapidly growing into a market leader, especially in provinces in East Java, Central Java, West Java, and Bali, and plans to expand nationally. This study aims to analyze consumer perceptions of healthy food taste quality and service quality at Mie Gacoan Citra Raya outlet, Tangerang. The method used is descriptive qualitative research, with data collection through in-depth interviews, participatory observation, and documentation. The results showed that product quality, especially taste, texture, portion, and cleanliness of presentation, played an important role in consumer satisfaction. Although most consumers were satisfied with the taste served, there were some complaints regarding flavor instability, such as varying levels of spiciness. On the other hand, service quality also had a major influence on consumer experience, with some branches demonstrating good service, while others faced constraints in internal communication and resource management. This study suggests that Mie Gacoan should review its product and service quality standards to improve customer satisfaction and strengthen the company's reputation in a competitive market.